2021
DOI: 10.1111/jfpp.15953
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of process and product parameters on physical attributes, resistant starch, and in vitro starch digestibility of modified rice flour‐based extruded snacks

Abstract: Modified rice flour (MRF) with higher resistant starch content was explored to produce resistant starch, enriched extruded snacks. Effects of feed moisture (10%–35%), temperature (130–180°C), and screw speed (150–200 rpm) on specific mechanical energy input (SME), expansion ratio (ER), breaking strength (BS), L*, a*, and b* values, resistant starch (RS), predicted glycemic index (pGI), glycemic load (GL), and sensory evaluation of extrudates were investigated. Moreover, independent variables influenced both ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…SEI, a physical property, measures the amount of puffing in an extruded snack after extrusion (Gulzar et al , 2021). Extrusion cooking results in extrudates with porous expanded structures due to sudden drop in pressure at die which causes rapid flash off of internal moisture leading to formation of air pockets within the sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SEI, a physical property, measures the amount of puffing in an extruded snack after extrusion (Gulzar et al , 2021). Extrusion cooking results in extrudates with porous expanded structures due to sudden drop in pressure at die which causes rapid flash off of internal moisture leading to formation of air pockets within the sample.…”
Section: Resultsmentioning
confidence: 99%
“…BS represents the hardness of extruded snacks (Gulzar et al , 2021). Extrudates with low hardness and consequently lower BS values are preferred (Ruskova et al , 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Escobedo et al (2020) reported a reduction of RS in black beans after extrusion, attributing that this could correspond to the destruction of RS1 and RS2 (native RS); besides during thermal treatments, protein amino groups could interact with starch carbonyl groups through hydrogen and covalent bonds, thus hindering complete starch retrogradation, because of the protein–starch interactions, resulting in reduction of RS content. Gulzar et al (2021) studied how the extrusion process and parameters used during extrusion could affect the RS content in rice-flour-based extruded snacks, finding that the different parameters used during extrusion affected differently the RS content; for instance, the increase of temperature from 130 to 180 °C increased significantly from 6.84% to 7.78%, while the RS content decreased from 6.40 to 6.21% with an increase in screw speed from 50 to 150 rpm. Furthermore, during extrusion starch gelatinization can be generated, resulting in an increase in starch digestibility (90%); in addition, extrusion can cause a cleavage of amylose and particularly of amylopectin molecules induced by the shear, resulting in smaller and more digestible fragments (dextrins and reducing sugars) .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Higher the SME, higher is the extent of starch gelatinization, which subsequently results in the expansion of extrudate (Pardhi et al , 2019). Therefore, for expanded products, higher SME is preferred (Gulzar et al , 2021). For developed extrudates, the mean values of SME ranged between 58.8 kWh/kg and 76.1 kWh/kg (Table SI in the online supplemental materials).…”
Section: Effect Of Independent Variables On System and Product Responsesmentioning
confidence: 99%